PENGARUH PENDAPATAN PERKAPITA, INDEKS PEMBANGUNAN MANUSIA DAN PERTUMBUHAN EKONOMI TERHADAP JUMLAH PENDUDUK DI KOTA BANJARMASIN - Norsyahida Sari; Ahmad Yunani (PPJP Universitas Lambung Mangkurat, 2020)
This research aims to know and analyze how much income per capita, human development index, and economic growth of population in Banjarmasin city.The method used in this research is the quantitative method, with variable income per capita, human development index and economic growth of population in Banjarmasin, Data Time series secondary take 10 ( Ten) years with data analysis techniques using multiple linear regression, with the test of assumptions The results showed that the revenue of the Percapita and Human Development Index were partially influential on the population in Banjarmasin but economic growth did not have a partial effect on the number of inhabitants in the city Banjarmasin. The Percapita revenue, Human development index and economic growth simultaneously influence the number of inhabitants in Banjarmasin city and the variable that is dominant influence on the number of inhabitants in Banjarmasin city is the index Human development.Keywords: percapita income, human development index, economic growth and number of inhabitants in Banjarmasin city